Expert opinions on improving coercion data collection across Europe: a concept mapping study - Lickiewicz, Jakub; Efkemann, Simone Agnes; Husum, Tonje Lossius; Lantta, Tella; Pingani, Luca; Whittington, Richard (Frontiers in Psychiatry, 2024)
Introduction: Coercion is frequently used in mental health practice. Since it overrides some patients' fundamental human rights, adequate use of coercion requires legal and ethical justifications. Having internationally standardised datasets to benchmark and monitor coercion reduction programs is desirable. However, only a few countries have specific, open, publicly accessible registries for this issue. Methods: This study aims to assemble expert opinions regarding strategies that might be feasible for promoting, developing, and implementing an integrated and differentiated coercion data collection system in Europe at national and international levels. A concept mapping methodology was followed, involving 59 experts from 27 countries in generating, sorting and rating strategies regarding relevance and feasibility. The experts were all researchers and/or practitioner members of an EU-COST-Action focused on coercion reduction Fostering and Strengthening Approaches to Reducing Coercion in European Mental Health Services (FOSTREN).Results: A hierarchical cluster analysis revealed a conceptual map of 41 strategies organized in seven clusters. These clusters fit into two higher-order domains: "Advancing Global Health Research: Collaboration, Accessibility, and Technological Innovations/Advancing International Research" and "Strategies for Comprehensive Healthcare Data Integration, Standardization, and Collaboration." Regarding the action with the higher priority, relevance was generally rated higher than feasibility. No differences could be found regarding the two domains regarding the relevance rating or feasibility of the respective strategies in those domains. The following strategies were rated as most relevant: "Collection of reliable data", "Implementation of nationwide register, including data on coercive measures", and "Equal understanding of different coercive measures". In analysing the differences in strategies between countries and their health prosperity, the overall rating did not differ substantially between the groups.Conclusions: The strategy rated as most relevant was the collection of reliable data in the nationwide health register, ensuring that countries share a standard understanding/definition of different coercive measures. Respondents did not consider the feasibility of establishing a shared European database for coercive measures to be high, nor did they envision the unification of mental health legislation in the future. There is some consensus on the most suitable strategies that can be adopted to enable international benchmarking of coercion in mental health settings.